EVALUATION OF THE IMPLEMENTATION OF THE PATTERNS IN THE WOMEN’S WATER POLO: THE EXPERIENCE OF A TEAM IN THE ITALIAN CHAMPIONSHIP PREMIER LEAGUE (Fiep Bulletin - online, 2014)
In water polo lacks a codified methodology for tactics training, which is thus only left to coach’s discretion.Nine women water polo matches, during season 2011/2012 (Italian female Serie A1), have been analyzed by a water polo coach, helped by a statistician and a performance analyst. Purpose of the analysis process was to identify single events during the matches, to examine the tactical pattern implemented in this events, to obtain by the coach an evaluation on tactical pattern compliance and then to put this compliance in relation to event’s outcome. Aim of the work is to verify the efficacy of different attack patterns, when they were wellperformed, in order to create a codified methodology for teaching water polo through tactics. The research approach is integrated and consists of 3 distinct methods: case study (9 matches of the Italian Serie A1 Women’s Championship, season 2011/2012, played by the Volturno sc) for the analysis of matches, action research method for coach contribution, and theoretical-argumentative method to deduce a theoretical framework in which define the data  processing. The research team examined matches with Dartfish TeamPro, isolating single keyframes relative to attack events, identifying the implemented attack pattern, then the coach expressed an evaluation on attack patte rn compliance. The results showed a general efficacy of tactical patterns (when they are well performed), but showed significant differences within correlation coefficients of single patterns, confirming the need for developing a common methodology for teaching waterpolo through tactics.
Keywords: videoanalysis; water polo tactis; performances